Effects of an inner stationary cylinder having an elastic rod-like extension on the mixed convection of CNT-water nanofluid in a three dimensional vented cavity - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2019)
Numerical study for the effects of an inner stationary cylinder having an elastic rod like extension on the mixed convection of CNT-water nanofluid in a three dimensional vented cavity was performed by using finite element method. Effects of various pertinent parameters such as Reynolds number (between 100 and 1000), elastic modulus of the flexible rod (between 10(5) and 10(8)), size of the elastic rod (between 0.05H and 0.3H), size of the circular cylinder (between 0.025H and 0.25H), inclination angle of the left vertical surface of the cavity (between 0 degrees and 30 degrees) and CNT-nanoparticle solid volume fraction (between 0 and 4%) on the convective flow features in a 3D vented cavity were analyzed. It was observed that with the installation of the obstacle (cylinder + elastic rod) and changing its geometrical and other parameters (elasticity of the rod) affect the variations of established multiple re-circulation zones and isotherms with the three dimensional vented cavity. The average heat transfer rate for the left vertical surface deteriorated with higher inclination angle of the side surface of the cavity while the variations in the average heat transfer rate for the upper surface was found to be slight. Inclusion of the CNT nanoparticle results in average heat transfer enhancement which is about 60% at the highest nanoparticle solid volume fraction and the rate of enhancement was found to be independent of obstacle geometrical parameters, elasticity of the flexible wall and side surface inclination angle of the cavity. A correlation for the average Nusselt number is obtained in polynomial form for the configurations in the presence and absence of obstacles. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: CNT - water nanofluid; Vented cavity; Finite element method; Obstacle